Decarbonisation at home: The contingent politics of experimental domestic energy technologies. (October 2016) - Bickerstaff, Karen; Hinton, Emma; Bulkeley, Harriet
Policy efforts to reduce the carbon intensity of domestic energy consumption have, over the last three decades, been dominated by an almost dichotomous reading of the relationship between technology and social change. On the one hand, there is a conception of personal responsibility that constructs domestic energy users as key actors in the adoption and (appropriate) use of low carbon energy technologies; from this perspective, environmental change becomes a matter of mobilising personal capacities such that individuals make better choices. On the other hand, decarbonising homes is conceived to be an outcome of top-down infrastructural interventions, with householders (or end users) positioned as relatively passive agents who will respond to engineered efficiency in linear and predictable ways. In practice, both positions have been found wanting in terms of accounting for how (and why) change happens and in turn delivering on ambitious policy goals. The argument we develop in this article goes beyond critiquing these problematic framings of technology and the locus of agency. Drawing on three contrasting low carbon energy technology projects in the UK, we present an alternative perspective which foregrounds a more experimental, ad hoc and ultimately provisional mode of governing with domestic energy technologies. We reflect on the meaning and political implications of this experimental turn in transforming (and decarbonising) domestic energy practices.